Keanekaragaman dan peran fungsional serangga Ordo Coleoptera di area reklamasi pascatambang batubara di Berau, Kalimantan Timur - Gilang Aditya Rahayu; Damayanti Buchori; Dadan Hindayana; Akhmad Rizali (Jurnal Entomologi Indonesia, 2017)
Reclamation has an important role in the recovery of mined land ecosystems and is expected to restore the diversity of insects such as Coleoptera. Reclamation process can change Coleoptera diversity and formed communities new of functional groups. The objective of this research was to study the diversity, functional role, and composition of the Coleoptera in the reclamation area. This ecological research was conducted in reclamation area of PT. Berau Coal in Binungan, Berau District, East Kalimantan. Several ages of reclamation area were selected for observation i.e. 2, 4, 6, 8 and 10 years and also natural forest as comparison. Insects were sampled using pitfall trap and malaise trap in a 100-meter transects for each age revegetation. The results showed that there is no difference in the diversity of Coleoptera between age of reclamation. Age of reclamation tend to affect the composition species and functional role of Coleoptera. Abundance of predatory Coleoptera show differences in different reclamation ages, while the abundance of other functional group (herbivor  detritivor and mycophagus) does not seen to be influenced by age of reclamation. Nevertheless, there is an increasing trend of Coleoptera abundance of herbivores and detritivor group with increasing age reclamation.